A PERSPECTIVE ON THE ILO CONVENTION ON THE ELIMINATION OF FORCED OR COMPULSORY LABOUR: THE CASES OF NIGERIA AND CAMEROON - Cynthia, L. Siona Ndeh; Bukoye, Teslim O. (European Scientific Journal, ESJ, 2015)
Since its inception in 1919, the International Labour Organization (ILO) has promoted worldwide eradication of forced or compulsory labour as one of its primary objectives. Given its status as a universal and core international labour standard as promulgated within the ILO’s 1998 Declaration on Fundamental Principles and Rights at Work, the Convention on the Eradication of Forced Labour or Compulsory Labour has so far been ratified by many member states, including Nigeria and Cameroon. Here, the concept of forced labour is distinguished from the practice of labour exploitation, which is equally common within less developed economies. This article examines the implementation level within both nations as actors in the struggle against forced labour in the twenty-first century and the reality of implementing the Convention on the eradication of forced or compulsory labour within their respective legal systems. Examining the efforts put in by both nations till date will equally shed light and contribute to the discussion on the implementation process of the ILO’s core labour standards and challenges faced, particularly within the context of developing economies.